In situ synthesis of ligand reduced/capped silver nanoparticles and the effect of temperature and ligand structure on the size of silver nanoparticles - Kasture, M. B.; Patel, P.; Prabhune, Asmita; Ramana, C. V.; Kulkarni, A. A.; Bhagavatula L. V. Prasad (Journal of Chemical Sciences, 2008)
We report in situ synthesis of silver nanoparticles using biosurfactants called sophorolipids as reducing and capping agents. We further study the effect of temperature and the structure of sophorolipid on the size of silver nanoparticles obtained. The silver nanoparticles were characterized by UV-visible, transmission electron microscope (TEM) and light scattering (DLS) analysis techniques.
Keywords: dynamic light scattering; Nucleation and growth; silver nanoparticles; Sophorolipid

Synthesis of triangular gold nanoplates: role of bromide ion and temperature - Kumar, D. V. Ravi; Kulkarni, Amol A.; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2013)
Synthesis of noble metal triangular nanoplates is a kinetically controlled process in which temperature and packing defects play a major role. Nucleation and growth process of kinetically controlled reaction can be greatly influenced by temperature affecting the yield and edge length of the triangles. Through a conventional batch mode process, here we study the effect of temperature on nucleation and growth of gold triangular nanoplates and obtain some insight of the temperature effects on the final yield and edge length of triangles. The role of Br- ions in the synthesis of triangular nanoplates is studied by varying the amount of CAB and by replacing the CTAB with HBr. The results show that, while CTAB controls the edge length and yield of triangles, its use is not mandatory to attain plate like morphology. Finally we show that, while the initial temperature of the reaction mixture governs the nucleation rate and the rate of temperature rise governs the growth rate of particles, they along with the concentration of Br- ions control the edge length and yield. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Au nanotriangles; Halide ion effect; heat transfer; Kinetically controlled; Nature of gold precursor complex; Nucleation and growth; Optical properties

Enhanced stability of sodium metal anodes in covalent triazine frameworks via progressive nucleation with optimized conducting composite matrix - Wasnik, Kundan; Bhatt, Rajesh C.; Shelke, Manjusha V. (Small, 2025)
Organic materials offer exciting possibilities to improve rechargeable battery performance in multiple ways. This study explores the Covalent Triazine Framework (CTF) as an interlayer to modulate progressive sodium nucleation and subsequent recurrent deposition/extraction in an anode-less sodium battery. The optimized composite, C60R40, which combines CTF with reduced graphene oxide (rGO), has demonstrated its effectiveness as a host. In half cell Na electrodeposition, the C60R40 host exhibits 99.9% coulombic efficiency at an applied current density and areal capacity of 6 mA cm-2 and 2 mAh cm-2, respectively, for 500 cycles. The stable performance is also observed in both full-cell and anode-less battery configurations. When paired with Na3V2(PO4)2F3, the sodium-plated C60R40 demonstrated a stable discharge capacity of 110 mAh g-1. Furthermore, the anode-less sodium battery configuration, with Na3V2(PO4)3 cathode, achieved a promising discharge capacity exceeding 50 mAh g-1 without any additional modifications. These findings highlight the significant role of organic materials in improving the performance of rechargeable sodium metal batteries.
Keywords: anode-less batteries; CTF; instantaneous and progressive nucleation; Nucleation and growth; SEI